THE ROLE OF POLITICAL LAWS IN LAW CODIFICATION AND UNIFICATION EFFORTS FOR THE DEVELOPMENT OF NATIONAL LAW IN ACCORDANCE WITH PANCASILA AND THE PRINCIPLES OF DIVERSITY IN INDONESIA - Anajeng Esri Edhi Mahanani (Surakarta Law and Society Journal, 2020)
Article aims to analyze and assessing political role of law in an effort to codification and unification of the law for the construction of national law in accordance with Pancasila and the principle of diversity of Indonesia. This research is a prescriptive normative research, using literature study. The results of the discussion concluded that the codification and unification needed in Indonesia with the condition that the plurality of the people are partial and open codification and unification. Based on the results of the discussion it can be said that: First, the development of national law requires the reconstruction of law based on the Pancasila and the Constitution of the 1945 Constitution of the Republic of Indonesia, so that the colonial law which is still in force today must immediately be restructured based on the Ideology and the National Constitution. Second, it is necessary to realize an open unification and codification in the development of Political Laws based on Pancasila and the value of Indonesian Diversity. Keywords: codification, Pancasila, legal development, political law.